2017
DOI: 10.15252/emmm.201606261
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3 an important player in fibrogenesis and therapeutic target for idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal parenchymal lung disease with limited therapeutic options, with fibroblast‐to‐myofibroblast transdifferentiation and hyperproliferation playing a major role. Investigating ex vivo‐cultured (myo)fibroblasts from human IPF lungs as well as fibroblasts isolated from bleomycin‐challenged mice, Forkhead box O3 (FoxO3) transcription factor was found to be less expressed, hyperphosphorylated, and nuclear‐excluded relative to non‐diseased controls. Downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 44 publications
4
77
0
Order By: Relevance
“…FOXO3 is hyperphosphorylated and down‐regulated in IPF fibroblasts. Moreover, knockdown of FOXO3 in normal fibroblasts reproduces IPF fibroblast phenotype . In the current study, we found ASV or inhibition of PI3K/Akt pathway could significant suppress TGF‐β1 caused FOXO3 hyperphosphorylation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…FOXO3 is hyperphosphorylated and down‐regulated in IPF fibroblasts. Moreover, knockdown of FOXO3 in normal fibroblasts reproduces IPF fibroblast phenotype . In the current study, we found ASV or inhibition of PI3K/Akt pathway could significant suppress TGF‐β1 caused FOXO3 hyperphosphorylation.…”
Section: Discussionsupporting
confidence: 54%
“…Accumulation of collagen and increased expression of α‐SMA is associated with FOXO3a inactivation . Moreover, suppressed FOXO3a activity resulting from hyperphosphorylation of FOXO3a by Akt was found closely linked to the progression of IPF . However, limited evidence linked the relationship between FOXO3a and EMT in pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies support the notion that FoxO family members act synergistically with the TGF-b1 signaling pathway to promote gene expression of many targets in fibroblasts (21)(22)(23). Subsequent in vitro studies were therefore performed to study the effects of PFD treatment on the TGF-b1 signaling pathway in iPAH PA-SMCs.…”
Section: Pfd Increases Foxo1 Expression and Nuclear Localization In Imentioning
confidence: 94%
“…It has been reported Values are mean ± SD of three independent experiments. *P < 0.05, **P < 0.01, NS: not significant that the negatively regulatory mechanism of cell cycle is impaired in IPF patients [38]. In such a situation, stimulation by periostin may enhance cell proliferation of lung fibroblasts.…”
Section: Discussionmentioning
confidence: 92%